Posted by **stumped** on Wednesday, April 25, 2007 at 6:51pm.

3x-5(3x-7)= 2(x+9) + 45

3x-15x+35= 2x+18 +45

-12x + 35 = 2x+63

-12x -28 = 2x

-12 -28 =x

-40 =x

3x-5(3x-7)= 2(x+9) + 45

3x-15x+35= 2x+18 +45

-12x + 35 = 2x+63

-10x+35=63

-10x=28

x=-2.8

you are both wrong!

3x - 15x + 35 = 2x + 18 + 45

-12x - 2x = 63 - 35

-14x = 28

x = -2

test my answer, it works

- algbrea -
**teresa**, Sunday, November 8, 2009 at 8:43pm
18x+13/4-17x-19/36

## Answer this Question

## Related Questions

- Math - Can you correct the errors? 4(x+3)=24 4(3x)=24 12x=24 12x/12= 24/12 X=2 5...
- bobpursly, - Is this correct now after i revised it Multiply. 3xy^2(5xy-4x+6y) ...
- Algebra - I have worked this and checked it and it does not come out true any ...
- Algebra 1b! - 1. Find the excluded value of x for the polynomomial expression ...
- algebra2 - 1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators ...
- algebra1 - could you walk-through the steps to solving this problem because I am...
- Algebra 2 - Factor each quadratic equation: 8x^2+10x-3 25x^2+10x-3 9x^2-15x-14 ...
- Algebra 1 - 1) what is the simplified form of (x-2)(2x+3)? Use the distributive...
- Math to hard please help - Add or subtract (4x^2+15x-3)-(3x^2+5) A. 7x^2+15x-8 B...
- math - solve each of the following equations by factoring and show your work 12x...

More Related Questions